The History of Serbia: Political and Ecclesiastical (Prof. SEP dr. Georgios Nektarios At. Lois, Hellenic Open University, Patras, 2017) - Angelopoulos, Athanasios (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The History of Serbia: National and Ecclesiastical (original title: ΙΣΤΟΡΙΑ ΤΗΣ ΣΕΡΒΙΑΣ ΠΟΛΙΤΙΚΗ ΚΑΙ ΕΚΚΛΗΣΙΑΣΤΙΚΗ) published by Έννοια, Athens is a unique book in Greek bibliography covering the history of Serbia in Southeast Europe from its beginning to the present day. The concept of unity and interconnection of the national and ecclesiastical history of the Serbian nation, permeated with noble tradition, democratic spirit, deeply rooted in Orthodox Christian beliefs, adds distinctive flavour to this impressive research.